Direct Observation of Strand Passage by DNA-Topoisomerase and Its Limited Processivity - Yogo, Katsunori (Public Library of Science, 2012)
Type-II DNA topoisomerases resolve DNA entanglements such as supercoils, knots and catenanes by passing one segment of DNA duplex through a transient enzyme-bridged double-stranded break in another segment. The ATP-dependent passage reaction has previously been demonstrated at the single-molecule level, showing apparent processivity at saturating ATP. Here we directly observed the strand passage by human topoisomerase IIα, after winding a pair of fluorescently stained DNA molecules with optical tweezers for 30 turns into an X-shaped braid. On average 0.51±0.33 µm (11±6 turns) of a braid was unlinked in a burst of reactions taking 8±4 s, the unlinked length being essentially independent of the enzyme concentration between 0.25–37 pM. The time elapsed before the start of processive unlinking decreased with the enzyme concentration, being ∼100 s at 3.7 pM. These results are consistent with a scenario where the enzyme binds to one DNA for a period of ∼10 s, waiting for multiple diffusional encounters with the other DNA to transport it across the break ∼10 times, and then dissociates from the binding site without waiting for the exhaustion of transportable DNA segments.